2018
DOI: 10.1371/journal.pone.0198601
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sensory neuronal groups in CGRP-cre-ER reporter mice: Comparison to Nav1.8-cre, TRPV1-cre and TRPV1-GFP mouse lines

Abstract: Peptidergic sensory neurons play a critical role in nociceptive pathways. To precisely define the function and plasticity of sensory neurons in detail, new tools such as transgenic mouse models are needed. We employed electrophysiology and immunohistochemistry to characterize in detail dorsal root ganglion (DRG) neurons expressing an inducible CGRPcre-ER (CGRP-cre+); and compared them to DRG neurons expressing Nav1.8cre (Nav1.8-cre+), TRPV1cre (TRPV1-cre+) and TRPV1-GFP (V1-GFP+). Tamoxifen effectively induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
116
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(131 citation statements)
references
References 64 publications
13
116
2
Order By: Relevance
“…1,4,9,27,41 Pain conditions trigger plasticity of sensory neurons via transcriptional, translational, and posttranslational mechanisms. Accordingly, sensory neuron subgroups have distinct transcriptomes, biochemical makeup, electrophysiology profiles and functions in naïve animals and humans.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,4,9,27,41 Pain conditions trigger plasticity of sensory neurons via transcriptional, translational, and posttranslational mechanisms. Accordingly, sensory neuron subgroups have distinct transcriptomes, biochemical makeup, electrophysiology profiles and functions in naïve animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…1 Interestingly, recent single-cell data suggest that there are two types of MrgprA3 + DRG neurons: a first MrgprA3 + subgroup has both TRPV1 and TRPA1, while a second MrgprA3 + subgroup, which is represented by lesser number of neurons, express only TRPV1. 46 Recent single-cell RNA-sequencing data 27 and electrophysiology profiling of DRG sensory neurons 4 showed that there are two distinct MrgprD + subgroups (S4 and S5) representing C-mechano-heat and C-mechanosensitive nociceptors 46 . The second subgroup is MrgprD + DRG neurons, which are itch-sensing neurons 45 and also encode C-mechano-heat nociceptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations